Iridescence as Affordance: On Artefacts and Light Interference in the Renewal of Life Among the Owa (Eastern Solomon Islands). Issue 1 (14th February 2018) - Revolon, Sandra
Abstract : This article focuses on identifying the technical and cognitive processes that imbue artefacts and practices with forms of efficacy central to the relations the Owa people have with surrounding invisible entities. In particular, it aims to describe the correspondences between the schemas at work, on the one hand, in material logics, by analysing the making of magical artefacts and, on the other hand, in ritual logics, through an analysis of the practices and representations involved in Owa rituals. These two domains – technical action and ritual action – are both locally understood as ways of acting on and in the world. This efficacy rests on the relationships established between vital processes and technical processes, or more precisely on the co‐construction, by specialized humans and by invisible entities, of artificial devices that reproduce visible phenomena considered by the Owa to be visible manifestations of powerful entities' effective capacity to intervene ( mana ‐ity/ mana ‐ization) in the world. These include a broad category of phenomena that can be seen in the atmosphere and on the bodies of living organisms and which all display, in different ways, chromatic distortions that are mobilized and imitated by Owa carvers, who apply them to the surface of magical artefacts. By illustrating one of the ways in which Owa craftsmen imitate vital processes through artefacts, this article examines what this imitation indicates about how the Owa conceive the renewal of life and act upon life in an attempt to control it. The idea of 'vital processes' should be understood here in a broad sense to include all the processes that benefit life and result from non‐human action.